Multicultural personality traits of Chinese university students and their effects on the psychological adjustment in the aftermath of COVID-19 in Shanghai: a scale validation - Fu, Hanzhi; Nadeem, Muhammad Umar; Kulich, Steve J. (Frontiers in Psychiatry, 2024)
Objective: This study aims to explore Chinese university students’ multicultural personalities and examine how they predict the psychological adjustment of students in Shanghai. In addition, the validation of Multicultural Personality Questionnaire Short Form (MPQ-SF) scale developed to assess the multicultural personality traits of individuals is also aimed in Chinese context. Data were collected after the psychological stresses from restrictions imposed by COVID-19 in China that influenced life adjustments for nearly three years. Method: A total of 1,099 university students participated in this multi-stage study. First, the Chinese version of MPQ-SF was developed and validated. The impact of MPQ-SF-C dimensions was then tested through path analysis to establish the effects of Chinese university students’ multicultural personality traits on their psychological adjustment using the Schwartz Outcome Scale (SOS-10). Results: The MPQ-SF-C yielded a five-factor solution which accounted for 60.14% of the common variance. The findings indicated that cultural empathy (β = 0.23, p < 0.05), certainty seeking (β = 0.13, p < 0.05), open-mindedness (β = 0.48, p < 0.05), and emotional stability (β = 0.24, p < 0.05) had significant influences on adjustment. Only flexibility was found to have a statistically insignificant impact on adjustment at this time in this context. MPQ-SF-C and SOS-10 scales represented very good psychometric properties in terms of their reliability and validity. Conclusion: The MPQ-SF-C shows good psychometric properties and appropriateness for evaluating multicultural personalities in Chinese contexts. The multicultural personality characteristics of university students using this scale well predicted their psychological adjustment.